MYCL is a target of a BET bromodomain inhibitor, JQ1, on growth suppression efficacy in small cell lung cancer cells - Kato, Fuyumi (Oncotarget, 2016)
We aimed to elucidate the effect of JQ1, a BET inhibitor, on small cell lung cancers (SCLCs) with MYCL amplification and/or expression. Fourteen SCLC cell lines, including four with MYCL amplification, were examined for the effects of JQ1 on protein and gene expression by Western blot and mRNA microarray analyses. The sensitivity of SCLC cells to JQ1 was assessed by cell growth and apoptosis assays. MYCL was expressed in all the 14 cell lines, whereas MYC/MYCN expression was restricted mostly to cell lines with gene amplification. ASCL1, a transcription factor shown to play a role in SCLC, was also expressed in 11/14 cell lines. All SCLC cell lines were sensitive to JQ1 with GI(50) values ≤1.23 μM, with six of them showing GI(50) values <0.1 μM. Expression of MYCL as well as MYCN, ASCL1 and other driver oncogenes including CDK6 was reduced by JQ1 treatment, in particular in the cell lines with high expression of the respective genes; however, no association was observed between the sensitivity to JQ1 and the levels of MYCL, MYCN and ASCL1 expression. In contrast, levels of CDK6 expression and its reduction rates by JQ1 were associated with JQ1 sensitivity. Therefore, we concluded that CDK6 is a novel target of JQ1 and predictive marker for JQ1 sensitivity in SCLC cells.